Effects of thrombomodulin alfa on hemostatic parameters in disseminated intravascular coagulation: Post hoc analysis of a phase 3 randomized controlled trial. Issue 7 (11th August 2020) - Ito, Takashi; Maruyama, Ikuro; Shimazaki, Shuji; Yamamoto, Yasuhiro; Aikawa, Naoki; Hirayama, Akio; Honda, Goichi; Saito, Hidehiko
Abstract: Background: The efficacy and safety of thrombomodulin alfa (TM‐α), a cofactor protein promoting thrombin‐mediated protein C activation, have been examined in a phase 3 randomized, double‐blinded, parallel‐group trial in Japan. We have previously reported that TM‐α is noninferior to heparin for the resolution of disseminated intravascular coagulation (DIC). Objective: To investigate the basis for the efficacy of TM‐α in the phase 3 clinical trial in Japan through post hoc analysis of coagulation and fibrinolysis parameters. Patients/Methods: The 227 patients of the full analysis set population described in the original phase 3 trial in Japan were included in this analysis. Changes in parameters between before and after TM‐α or heparin administration in each of the two patient groups, with underlying diseases of either hematologic malignancy or infection, were studied separately and results were compared between TM‐α and heparin treatment groups in a post hoc manner. Results: TM‐α administration did not prolong activated partial thromboplastin time but significantly decreased thrombin‐antithrombin complex levels compared with heparin treatment. TM‐α administration reduced consumption of endogenous anticoagulants such as antithrombin and protein C by DIC, compared with the heparin group. DIC scores were decreased in both TM‐α and heparin groups during the 6‐day treatment. Conclusion: TM‐α can alleviate intravascular coagulation and consumption of anticoagulants without extending coagulation times. This may be associated with the relatively low risk of bleeding during TM‐α treatment.